The Impact of Capital Structure and Dividend Policies on Firm Profitability and Shareholders Wealth (Journal of Advances and Scholarly Researches in Allied Education, 2026)
The research aimed at assessing the impact of capital structure and dividends on profitability and shareholder wealth through an approach that involved both qualitative and quantitative techniques. In the study, the impact of financial decision-making such as capital structure and dividends on organizational performance was considered important to be known. Primary data collection entailed use of semi-structured interviews with finance managers, executives, and investors' analysts, while the secondary data involved financial information from financial statements and annual reports of the selected companies. The results of qualitative data analysis indicated that capital structure, dividends, and retained earnings are among the most important elements that affect profitability and growth of organizations. From the findings obtained through quantitative data analysis, there exists a significant positive relationship between capital structure and dividends with profitability measures like ROA, ROE, and EPS. Furthermore, it was discovered that the dividend policy played more significance in wealth maximization compared to capital structure. Both the variables had statistical significance, hence making a major influence in the performance of the companies. Generally, it was learned from the study that proper financial management that entails effective use of the optimal amount of debt with dividends plays a major role in maximizing shareholders' wealth.